Correlation between Ultrasound-Measured Endometrial Thickness and Histopathological Findings in Postmenopausal Women with Abnormal Uterine Bleeding - Rizwana Rehman Bazai, Fahmida Umar, Shazia Saeed, Nazia Khan, Sajida Ghilzai, Palwasha Ali, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Abnormal uterine bleeding (AUB) in postmenopausal women is a clinically recognised symptom commonly associated with endometrial pathology (including malignancy). TVUS is a commonly used, noninvasive way of measuring endometrial thickness (ET), which may assist in directing further management. Nevertheless, additional evaluation is needed in local populations for the correlation between ET and histopathological findings. Objective: The aim is to investigate the correlation between ultrasound-measured endometrial thickness and the histopathological findings in postmenopausal women with AUB. Methods: A cross-sectional study was conducted in Shaikh Hospital and Bolan Medical College Hospital, Quetta, from February 2022 to June 2023. Transvaginal ultrasound and endometrial sampling were performed on seventy postmenopausal women with AUB. Correlation of biopsy-confirmed histopathology with et was recorded. It was also analyzed with demographic data and clinical biomarkers such as BMI, hemoglobin, fasting glucose, and serum estradiol. SPSS v26 was used to calculate Pearson correlation, sensitivity, specificity, and predictive values of ET thresholds. Results: The mean endometrial thickness was 8.7 ± 3.5 mm. The histopathology was 20 cases of hyperplasia without atypia, 10 with atypia, 10 carcinomas, and 30 benign diagnoses. For the detection of premalignant or malignant pathology, the sensitivity and NPV of ET ≥5 mm were 100%. There was a strong positive correlation between ET and histopathological severity (r = 0.76, p < 0.001). Patients with pathological findings had metabolic risk factors such as elevated BMI and glucose. Conclusion: TVUS-measured endometrial thickness is strongly correlated with histopathological abnormalities of postmenopausal AUB. Thus, a cutoff of ≥5 mm is highly sensitive and may be used as an effective triaging tool for endometrial sampling. Clinical and metabolic risk profiling may provide additional diagnostic accuracy when integrated as part of the assessment. Keywords: Postmenopausal bleeding, Endometrial thickness, Transvaginal ultrasound, Endometrial hyperplasia, Endometrial carcinoma, Histopathology, Obesity, Pakistan